A new FWM reduction technique based on damping selective wavelengths - Abed H.J.; Din N.M.; Al-Mansoori M.H.; Abdullah F.; Salim N.; Fadhil H.A. (National Academy of Sciences of Ukraine, 2023)
This paper proposes a new method that can suppress the four-wave mixing using an Optical Drop Multiplexing (ODM) technique. The four-wave mixing (FWM) behavior and the performance of wavelength division multiplexing (WDM) systems are investigated, using the proposed technique. It is found that the FWM power is drastically reduced to -96 dBm, when the ODM technique was used. For a WDM system at the first channel (193 THz), the suggested approach offered the bit error rate (BER) to be 1.47 10-27, in comparison with the absence of the current technique, where BER was 2.53 10-17. Moreover, it is found that the proposed technique caused the FWM power to reduce by 28 dB. HAIDER J. ABED, N.M. DIN, M.H. AL-MANSOORI, F. ABDULLAH, NOORA SALIM, HILAL A. FADHIL, 2013.